2022
DOI: 10.3389/fped.2022.885055
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Disease in Hospitalized Pediatric Patients With Acute Kidney Injury in China

Abstract: ObjectiveThe epidemiology and outcomes of acute kidney disease (AKD) after acute kidney injury (AKI) in hospitalized children are poorly described. The aim of this study is to investigate the prevalence, predictive factors, and clinical outcomes of AKD in hospitalized children with AKI.MethodsChildren (1 month–18 years) with AKI during hospitalization in the Second Xiangya Hospital from January 2015 to December 2020 were identified. AKD was defined based on the consensus report of the Acute Disease Quality Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 21 publications
8
14
3
Order By: Relevance
“…Exposure to sepsis, critical illness, hypovolemic shock and the need for mechanical ventilation increased the mortality signi cantly, with similar results previously published [23,24], while cancer and heart failure were the most signi cant susceptibilities encountered with impact on mortality. In the presence of a hospitalized patient, the physician should be aware of the risk of developing AKI keeping in mind that AKI is often a result of multiple renal insults.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Exposure to sepsis, critical illness, hypovolemic shock and the need for mechanical ventilation increased the mortality signi cantly, with similar results previously published [23,24], while cancer and heart failure were the most signi cant susceptibilities encountered with impact on mortality. In the presence of a hospitalized patient, the physician should be aware of the risk of developing AKI keeping in mind that AKI is often a result of multiple renal insults.…”
Section: Discussionsupporting
confidence: 85%
“…In our cohort we report a high incidence of AKD (17.8%). The severity of AKI and the extension in time of increased serum creatinine is associated with worse outcome as previously published in AWAKEN [3], AWARE [4], Baby-Ninja [7], AKI-EPI [21] studies as well as in many other regional studies in both critically and non-critically ill patients [1,14,22,23].…”
Section: Discussionmentioning
confidence: 78%
“…Table 4 outlines pediatric and adult studies of AKD epidemiology, risk factors, and outcomes. Pediatric studies in special populations have shown variable incidence of AKD ranging from 6.2% in children undergoing cardiopulmonary bypass, 13% in nonkidney solid organ transplant recipients, 15.6% in children with severe malaria infection, 35.3% in allogeneic hematopoietic stem cell recipients, and 42.3% in hospitalized children with AKI (16,(27)(28)(29)(30). Adult studies have shown even more variability with incidence ranging from 3.8% in the general adult population of a single Canadian territory to 4.4%-74% in adults of special populations including those undergoing cardiac and non-cardiac procedure, chemotherapy, hematopoietic stem cell transplant recipients, those with AKI, heart failure, sepsis, cirrhosis, and SARS-CoV-2 infection (20).…”
Section: Epidemiology Of Akdmentioning
confidence: 99%
“…Risk factors for AKD in children have not been widely studied. Few studies that have been published demonstrated a higher risk of AKD in children with higher stages of AKI with one study showing that stage of AKI predicted AKD in a graded manner (16,27,29). Though stage of AKI has been shown to be an important risk factor for progression to AKD, studies in adults and children have shown patient-level and acquired risk factors independently increased risk of AKD independent of AKI stage suggesting that patients with lower stages of AKI also deserve close evaluation for AKD risk.…”
Section: Epidemiology Of Akdmentioning
confidence: 99%
See 1 more Smart Citation